Analisis Karakteristik Kebahasaan dan Teknik Penceritaan dalam Memoar Broken Strings Karya Aurelie Moeremans - Nazwa Aidilia Octa Mevia; Claudia Agatha br Tarigan; Triwanti Andini Hutasoit; Jonatan Rio Gultom (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to comprehensively analyze the linguistic characteristics and storytelling techniques in the memoir Broken Strings by Aurélie Moeremans. This memoir shares a profound true story of the author's experience surviving emotional manipulation, coercive control, and psychological abuse in a toxic relationship. Using a qualitative descriptive method combining stylistic and structural narratology approaches, this study examines expressive diction, figurative language, and intrinsic narrative elements such as theme, point of view, plot pacing, and characterization. The results show that the author frequently exploits restrictive diction and uses similes and metaphors (such as